2007
DOI: 10.1093/schbul/sbm124
|View full text |Cite
|
Sign up to set email alerts
|

The Maudsley Early Onset Schizophrenia Study: Cognitive Function Over a 4-Year Follow-Up Period

Abstract: Generalized cognitive deficits have been consistently reported in adolescents with early onset schizophrenia (EOS; defined as onset before the age of 17 years). The impact on cognition of potential interactions between disease pathology and brain maturation remains unclear. We therefore compared cognitive function between 20 EOS patients and 20 healthy controls matched on age, gender, and parental socioeconomic status at 2 time points, when aged 15.58 (2.27) and after a mean interval of 4 +/- 1.08 years when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 66 publications
6
52
1
3
Order By: Relevance
“…The lack of significant differential development in verbal memory between EOS patients and healthy controls contrasts with previous findings [24]. However, we observed unexpected and significant deterioration of verbal memory in the healthy controls, and it is possible that tester-effects may explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The lack of significant differential development in verbal memory between EOS patients and healthy controls contrasts with previous findings [24]. However, we observed unexpected and significant deterioration of verbal memory in the healthy controls, and it is possible that tester-effects may explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…In continuation of these results on intelligence development, the focus of our current study is on the development of specific cognitive functions in EOS. Frangou et al (2008) reported a significant deterioration in immediate verbal memory and attention during the late adolescent years in EOS patients, while the performance in healthy controls improved. No differential change in the planning aspect of executive functions (EF) was observed, whereas information processing speed improved in EOS but not in controls [24].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…years after the onset of psychosis [16]. This finding of long-term stability in FSIQ is corroborated by similar, minor and statistical significant improvements in age-corrected FSIQ in EOS patients and controls over a mean interval of 4 years [14]. A possible explanation for the different findings may be methodological since previous longitudinal studies of intelligence in EOS and COS administered age appropriate childhood and adult IQ test versions.…”
Section: Discussionmentioning
confidence: 56%
“…A recent longitudinal study used a case-control design to assess the development of deficits in several domains of cognitive functioning, including intelligence, in adolescent patients with EOS using two time points of assessments with a mean interval of 4 years. A statistically significant, but relatively small improvement in mean FSIQ was found in patients and controls with no significant between-group difference in amount of change [14]. These longitudinal studies used age appropriate versions of Wechsler Intelligence Scales and age appropriate norms that make assessments of IQ from childhood and well into adulthood possible.…”
Section: Introductionmentioning
confidence: 99%